BERBAGAI FUNGSI ORGAN PENGAWAS DALAM KONSEP GOOD CORPORATE GOVERNANCE - Sofyan Syafri Harahap (Universitas Trisakti, 2001)
The efficacy of Board of Commissioner in executing its control funclion has many prob- lems. Due to the lack of expertise of members. To solve this issue, the regulator encour- ages to establish audit commitee to link Board of Commissioner Board of Director and intenal audit function. The paper discuss how to optimize the control function in